2007
DOI: 10.1096/fj.07-8189com
|View full text |Cite
|
Sign up to set email alerts
|

Globular structure of human ovulatory cervical mucus

Abstract: Human cervical mucus is a heterogeneous mixture of mucin glycoproteins whose relative concentration changes during the ovulatory phases, thereby producing different mucus aggregation structures that can periodically permit the transit of spermatozoa for fertilization. In preovulatory phase, mucus is arranged in compact fiber-like structures where sperm transit is hindered. Previously, through observations made of fixed and dehydrated samples, a permissive structure in the ovulatory phase was attributed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 25 publications
4
68
0
1
Order By: Relevance
“…Mucins have short hydrophobic domains (lipid-coated, nonglycosylated, cysteine-rich domains) interspersed between long glycosylated regions (5,32). The negatively charged glycosylated domains likely repel each other, but the hydrophobic domains may cause mucins to self-condense and/ or bundle together (33)(34)(35). To test this, we added 1% vol/vol of a nonionic detergent, (nonylphenoxy)polyethylene oxide, to the same mucus samples and again characterized the pore size.…”
Section: Cvm Mucins Are Condensed And/or Bundled Into Thick Cables Viamentioning
confidence: 99%
“…Mucins have short hydrophobic domains (lipid-coated, nonglycosylated, cysteine-rich domains) interspersed between long glycosylated regions (5,32). The negatively charged glycosylated domains likely repel each other, but the hydrophobic domains may cause mucins to self-condense and/ or bundle together (33)(34)(35). To test this, we added 1% vol/vol of a nonionic detergent, (nonylphenoxy)polyethylene oxide, to the same mucus samples and again characterized the pore size.…”
Section: Cvm Mucins Are Condensed And/or Bundled Into Thick Cables Viamentioning
confidence: 99%
“…Mucins are the main constituents of cervical mucus, while the concentration of other proteins starts to increase with progesterone secretion following ovulation. The pre-ovulatory fibrous structure of mucin becomes globular after ovulation, making it is less fibroelastic than its fibrous counterpart [14]. Mucus protein has been shown to have a non-Newtonian viscosity that is nonlinear with shear rate, such that it has strong resistance to deformation at low shear rates and weak resistance at high shear rates [15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, findings from the present study suggest that the sexual hormones may influence the changes in salivary flow rate and pH during ovulation phase. Electrolyte level, pH, buffer capacity, flow rate and ultra structure have been studied in saliva in reference to several diseases and physiological conditions (26)(27)(28)(29)(30)33,(36)(37)(38)(39)(40)(41)(42). The present study revealed the difference in the electrolytes, pH, buffer capacity and flow rate of saliva during the ovulation phase.…”
Section: Discussionmentioning
confidence: 61%